2021
DOI: 10.1186/s13018-021-02888-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of vascular endothelial growth factor as a prognostic and clinicopathological marker in osteosarcoma: a systematic review and meta-analysis

Abstract: Background In recent years, numerous investigations have been conducted to determine the clinical significance and critical functions of vascular endothelial growth factor (VEGF) in various malignant cancers. The purpose of this meta-analysis was to comprehensively evaluate the prognostic and clinicopathological value of VEGF in patients with osteosarcoma. Methods We performed a systematic literature retrieval of available databases. Odds ratios (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…VEGF can increase the permeability of blood vessels, which is beneficial for tumor cells entering blood vessels and flowing to all parts of the body (Zhou et al, 2021). It is found that, the elevated VEGF expression may be a predictive biomarker for poor prognosis and adverse clinicopathological characteristics in patients with osteosarcoma (Zhang et al, 2021). Results of this study showed that, the baicalein could down-regulate the VEGF protein expression in HepG2 cells.…”
Section: Effects Of Tt-acfm On Fluorescence Intensity Of Ros In Hepg2...mentioning
confidence: 70%
“…VEGF can increase the permeability of blood vessels, which is beneficial for tumor cells entering blood vessels and flowing to all parts of the body (Zhou et al, 2021). It is found that, the elevated VEGF expression may be a predictive biomarker for poor prognosis and adverse clinicopathological characteristics in patients with osteosarcoma (Zhang et al, 2021). Results of this study showed that, the baicalein could down-regulate the VEGF protein expression in HepG2 cells.…”
Section: Effects Of Tt-acfm On Fluorescence Intensity Of Ros In Hepg2...mentioning
confidence: 70%
“…The protein encoded by VEGFA can induce migration and invasion of vascular endothelial cells, which is crucial for tumor angiogenesis and metastasis 23 . High VEGFA expression indicates unfavorable prognosis in osteosarcoma patients 24 . Vimalraj et al 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 High VEGFA expression indicates unfavorable prognosis in osteosarcoma patients. 24 Vimalraj et al 25 reported that melatonin suppressed osteosarcoma angiogenesis via targeting VEGFA. Another study showed that MicroRNA-134 attenuated osteosarcoma angiogenesis and proliferation via inhibiting the VEGFA/VEGFR1 signaling pathway.…”
Section: Potential Hub Genes Of G-rg5 Against Osteosarcomamentioning
confidence: 99%
“…Currently, the traditional treatments still have limited success in clinical treatment. Herein, the question that which therapeutic strategy is more suit for osteosarcoma is worthy of further discussion, which may reveal new directions for osteosarcoma clinical treatment (Zhang et al,, 2021a).…”
Section: Introductionmentioning
confidence: 99%